2018
DOI: 10.1093/ehjqcco/qcy033
|View full text |Cite
|
Sign up to set email alerts
|

Causes of death in Japanese patients with atrial fibrillation: The Fushimi Atrial Fibrillation Registry

Abstract: In a Japanese community-based AF cohort, CV death was not mainly related to stroke but to heart failure. Non-CV death, mainly malignancy and infection, comprised more than a half of all deaths, which increased substantially in accordance with aging. Clinical factors that were associated with CV and non-CV death were distinct.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 24 publications
2
49
1
3
Order By: Relevance
“…Compared with previous cohort studies, [9][10][11][12] the patients in the present study were older, had a higher CHA2DS2-VASc score, a longer observation period, and equivalent OAC use and mortality. The causes of death were similar to those reported in previous studies, 9-12 including the predominance of non-CV death, malignant neoplasm, heart failure, and pneumonia, and fewer stroke deaths.…”
Section: Cause Of Death In Elderly Af Patientscontrasting
confidence: 67%
“…Compared with previous cohort studies, [9][10][11][12] the patients in the present study were older, had a higher CHA2DS2-VASc score, a longer observation period, and equivalent OAC use and mortality. The causes of death were similar to those reported in previous studies, 9-12 including the predominance of non-CV death, malignant neoplasm, heart failure, and pneumonia, and fewer stroke deaths.…”
Section: Cause Of Death In Elderly Af Patientscontrasting
confidence: 67%
“…Our data indicate that there will be 2318 new cases of AF in Toyama prefecture each year, and 40% will have a high risk of stroke and a guideline recommendation for OAC. In current practice, OAC prescription is low: the reported OAC prescription rate from the Fushimi AF Registry was 55% despite a mean CHA 2 DS 2 -VASc score of 3.4, 26 and the Shinken Database reported OAC prescription rates of 46%. 5 Furthermore, analysis of the J-Rhythm registry, Fushimi AF registry, and the Shinken database identified a high rate of stroke (18.4 per 1000 person-years) in AF patients with a CHA 2 DS 2 -VASc score ≥2 not receiving OAC.…”
Section: Discussionmentioning
confidence: 99%
“…In the frail group, we found that non-cardiac death increased significantly compared with the non-frail group. In past reports, mortality due to undetermined cause increased substantially in accordance with age, and non-cardiovascular death was most strongly associated with anaemia 20. This report may indicate that more careful follow-up of major bleeding events is necessary after DOAC administration in older patients.…”
Section: Discussionmentioning
confidence: 56%